Dad goes to school - McNamara, Margaret; Gordon, Mike (New York : Aladdin Paperbacks, 2007)
During Parents Week at Robin Hill School, the students are all impressed with what one another's parents do for a living, especially Ayanna, who realizes that the artwork her father does at home makes him very special.
Keywords: Occupations -- Fiction; Parents -- Fiction; Artists -- Fiction; Schools -- Fiction